b western nun talks on practical Buddhism /c - Palmo, Tenzin
Tenzin Palmo outlines the core principles of Tibetan Buddhism to newcomers and shows how we can train our minds through meditation. She also explores some of the difficulties Westerners face with finding and following a spiritual master, understanding karma, and being a woman on the Buddhist path.
Keywords: Tenzin Palmo, -- 1943; Buddhist nuns -- Biography; Buddhism -- China -- Tibet Autonomous Region